Assessment of Flood Susceptibility Analysis Using Geographical Information System (GIS) and Analytical Hierarchy Process (AHP) in Kota Belud Area, Sabah, Malaysia - Kamilia Sharir; Amirah Saidin; Rodeano Roslee (Geography, Earth Science and Environment: Research Highlights Vol. 1, 2024)
A flood susceptibility map is an instrument for assessing flood levels. Flood susceptibility maps can be developed using the Geographical Information System (GIS) because this can manipulate multi-dimensional natural hazard phenomena using a spatial element. This study aims to assess the flood susceptibility analysis using a GIS-based-heuristic analysis, namely the Analytical Hierarchy Process (AHP) model. The study was carried out in Kota Belud, Sabah, Malaysia. This area is known as a flood-prone area and cases of devastating flooding in Kota Belud, Sabah have been growing recently. Eight relevant physical parameters have been selected, namely, drainage density, drainage proximity, elevation, slope angle, slope curvature, land use, soil type, and topography wetness index. The relative importance of these factors has been compared in the pairwise matrix to gain weight values during the process of the Analytical Hierarchy Process (AHP). The flood susceptibility zones have been mapped according to their weightage value. Finally, the flood susceptibility map was prepared and classified into six classes very low, low, moderate, high, and very high susceptibility using the natural break classification method. In this study area, the very high susceptibility areas are located at the north, northwest and northeast, considerably flat in slope and low elevation as considered from DEM. By contrast, areas having a higher degree of slope angle are prone to flooding. The accuracy of the flood susceptibility model was validated using the Area Under the Curve (AUC) analysis. The AUC for success rate was estimated at 82.13%. This study concluded that the AHP model is suitable for the selection of land use suitability, control and manage the flood hazard/risk in the study area and potentially to be extended with different background environments. Strict measure needs to be taken concerning uncontrolled urbanization and the occupation of areas that have proximities to the rivers in order to prevent more significant damage.